Pendidikan Penyucian Jiwa Perspektif Ibnul Qayyim: Solusi Terhadap Kenakalan Remaja - Waluyo Erry Wahyudi (Indo Publishing, 2026)
This study examines the concept of tazkiyatun nafs (purification of the soul) according to Ibn al-Qayyim as a solution to juvenile delinquency. Employing a qualitative method with a library research approach, this study explores Ibn al-Qayyim’s major works, such as Madarij as-Salikin and Ighatsat al-Lahfan, to formulate principles of soul education relevant to the modern context. The findings reveal that tazkiyatun nafs consists of three main pillars: strengthening faith, controlling desires, and habituating righteous deeds. The application of these principles is believed to foster morally upright youth, reduce deviant behavior, and encourage the formation of a generation with integrity.